The impact of HIV/HCV co-infection on health care utilization and disability: results of the ACTG Longitudinal Linked Randomized Trials (ALLRT) Cohort - Linas, B. P. (2010)
HIV/hepatitis C virus (HCV) co-infection places a growing burden on the HIV/AIDS care delivery system. Evidence-based estimates of health services utilization among HIV/HCV co-infected patients can inform efficient planning. We analyzed data from the ACTG Longitudinal Linked Randomized Trials (ALLRT) cohort to estimate resource utilization and disability among HIV/HCV co-infected patients and compare them to rates seen in HIV mono-infected patients. The analysis included HIV-infected subjects enrolled in the ALLRT cohort between 2000 and 2007 who had at least one CD4 count measured and completed at least one resource utilization data collection form (N = 3143). Primary outcomes included the relative risk of hospital nights, emergency department (ED) visits, and disability days for HIV/HCV co-infected vs HIV mono-infected subjects. When controlling for age, sex, race, history of AIDS-defining events, current CD4 count and current HIV RNA, the relative risk of hospitalization, ED visits, and disability days for subjects with HIV/HCV co-infection compared to those with HIV mono-infection were 1.8 (95% CI: 1.3–2.5), 1.7 (95% CI: 1.4–2.1), and 1.6 (95% CI: 1.3–1.9) respectively. Programs serving HIV/HCV co-infected patients can expect approximately 70% higher rates of utilization than expected from a similar cohort of HIV mono-infected patients.